Tuning Multiscale Microstructures to Enhance Thermoelectric Performance of n‐Type Bismuth‐Telluride‐Based Solid Solutions. Issue 17 (18th June 2015) - Hu, Lipeng; Wu, Haijun; Zhu, Tiejun; Fu, Chenguang; He, Jiaqing; Ying, Pingjun; Zhao, Xinbing
<x xml:space="preserve">Abstract</x> Microstructure manipulation plays an important role in enhancing physical and mechanical properties of materials. Here a high figure of merit zT of 1.2 at 357 K for n‐type bismuth‐telluride‐based thermoelectric (TE) materials through directly hot deforming the commercial zone melted (ZM) ingots is reported. The high TE performance is attributed to a synergistic combination of reduced lattice thermal conductivity and maintained high power factor. The lattice thermal conductivity is substantially decreased by broad wavelength phonon scattering via tuning multiscale microstructures, which includes microscale grain size reduction and texture loss, nanoscale distorted regions, and atomic scale lattice distotions and point defects. The high power factor of ZM ingots is maintained by the offset between weak donor‐like effect and texture loss during the hot deformation. The resulted high zT highlights the role of multiscale microstructures in improving Bi2Te3‐based materials and demonstrates the effective strategy in enhancing TE properties.